The role of polyphosphates in the sequestration of matrix metalloproteinases. Issue 1 (17th April 2013) - McCarty, Sara M; Percival, Steven L; Clegg, Peter D; Cochrane, Christine A
Abstract This study outlines the potential of a novel therapeutic dressing for the management of chronic wounds. The dressing incorporates polyphosphate, a non toxic compound with a number of beneficial characteristics in terms of wound healing, in a foam matrix. The aim of this study was to identify the potential of polyphosphate incorporated in the foam dressing to sequester the activity of matrix metalloproteinases (MMPs) and proteases derived from Pseudomonas aeruginosa. Methods used included gelatin zymography and milk‐casein agar plate analysis. Results have shown that this dressing is effectively capable of reducing the levels of MMP‐2 and MMP‐9 in both their active and latent forms using an in vitro model. The dressing also demonstrated the compound's potential in the regulation of P. aeruginosa derived proteases.